MOFs materials as photocatalysts for CO2 reduction: Progress, challenges and perspectives - Mazhar Khan; Zeeshan Akmal; Muhammad Tayyab; Seemal Mansoor; Adnan Zeb; Ziwei Ye; Jinlong Zhang; Shiqun Wu; Lingzhi Wang (Carbon Capture Science & Technology, 2024)
Photocatalytic reduction of carbon dioxide (CO2) presents a pivotal solution to address meteorological and ecological challenges. Currently, metal-organic frameworks (MOFs) with their crystalline porosity, adjustable structures, and diverse chemical functionalities have garnered significant attention in the realm of photocatalytic CO2 reduction. This review provides a brief introduction to CO2 reduction and MOF material and their applications in CO2 reduction. Then, it undertakes a comprehensive examination of MOFs, summarizing their key attributes, including porosity, large surface area, structural multifunctionalities, and responsiveness to visible light, along with an analysis of heterojunctions and their methods of preparation. Additionally, it elucidates the fundamental principle of photocatalysis and CO2 reduction, encompassing both half and overall reactions. Furthermore, the classification of MOF-based materials is explored, along with the proposed mechanism for CO2 reduction and an update on recent developments in this field. Finally, this review outlines the challenges and potential opportunities for utilizing MOFs in CO2 reduction, offering valuable insights to scholars seeking innovative approaches not only to enhance CO2 reduction but also to advance other photocatalytic processes.